Inheritance of salt tolerance in cucumber (Cucumis sativus) - TIWARI, JAGESH K; MUNSHI, ANILABH D; KUMAR, RAVINDER; SHARMA, RAM KUMAR; SUREJA, AMISH K (The Indian Journal of Agricultural Sciences, 2011)
Inheritance pattern of salinity tolerance of cucumber was studied by combining ability and gene action analysis of salt-tolerant and salt-sensitive cucumber inbreds (produced through five generation of selfing) and its hybrids at two salinity levels, i e control (0.43 dS/m) and 4 dS/m. The higher values of general combining ability than that of specific combining ability, predictability ratio more than 0.5, average degree of dominance in between 0 and 1, and narrow sense heritability in between 50 and 100% indicated the predominance of additive gene action for salt tolerance in cucumber. The results demonstrate either hybridization and selection or simple recurrent selection methods for improvement of salinity tolerance in cucumber.